Cat-Scratch Disease: A Pitfall for Lymphoma Evaluation by FDG-PET/CT. (February 2017) - Dubreuil, Julien; Dony, Arthur; Salles, Gilles; Traverse-Glehen, Alexandra; Giammarile, Francesco; Skanjeti, Andrea
Abstract : Abstract: FDG-PET/CT is a standard of care in staging and response assessment of Hodgkin lymphoma. Hence, it is important to recognize pitfalls owing to the potential therapeutic impact. We report a case of a 29-year-old woman affected by stage III bulky Hodgkin lymphoma. The interim FDG-PET/CT showed a complete metabolic response. After three new cycles of chemotherapy, the patient showed fever and lymphadenopathy at clinic examination, PET/CT revealed several FDG uptakes at lymph nodes in inguinal and iliac region. Pathologic analyses, after biopsy and serologic examinations, led to the diagnosis of cat-scratch disease.